PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS EXPLAINDIO PADA MATERI GERAK PARABOLA DALAM UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF FISIKA SISWA SMA - Dephy Purwasari; Zulirfan Zulirfan; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : The purpose of this research is to develop learning media in the form of explaindio-based learning videos on parabolic motion material in an effort to improve the cognitive abilities of valid high school students' physics. The development of learning videos is carried out as a solution to the difficulties of learning physics, as well as the lack of use of learning media in the physics learning process. The type of research used is research and development (R&D) using the ADDIE model which consists of five stages, namely the analysis, design, development, implementation and evaluation stages. As for the ADDIE model research development scheme, the analysis stages are divided into needs analysis, problem analysis, and curriculum analysis. There are two design stages, namely the making of the History board and the making of the Story board. As for the development stage (Development) is the media development and validation stage. The validation aspect consists of aspects of learning theory, aspects of learning materials, and aspects of media. The data collection instrument was in the form of a validation sheet given to three validators. The data analysis technique is by calculating the average score of the validation assessment until all items are worth 3. The results of the second stage validation of all statement items in each aspect have received a minimum score of 3 for each aspect. The results showed that the explaindio-based learning video on parabolic motion material in an effort to improve the cognitive physics abilities of high school students that was developed met the valid criteria from the validated aspects including aspects of learning theory with an average score of 3.84, aspects of learning materials with an average score 3.38, and the media aspect with an average score of 3.4. So from the scores that have been described, the learning videos using the explaindio application are valid and suitable for use in the learning processKey Word : Learning Videos, Explaindio, Parabolic Motion